Evaluation of the performance of plumbing fixtures in public sports facilities in Brazil - Gonçalves, Felipe (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2020)
The performance of plumbing systems is directly related to water and energy consumption. Malfunction of components in these systems can cause water waste and discomfort to users. In this research, the performance of 607 plumbing fixtures was investigated in five public buildings focused on sports activities in the city of Joinville, Southern Brazil. The flow rates and leaks in all installed plumbing fixtures were verified. The measured flow rate values were compared to those established by Brazilian standards and by environmental certifications LEED and AQUA. Flow rates of showers with water at 40°±2 °C were measured in summer and winter to compare the performance of showers in different seasons. The flow rates in showers displayed worse performance in winter than in summer. Also, 30.9% of taps showed some type of leak and 77.8% of toilets trickled. Of all plumbing fixtures, 71.7% presented some kind of defect. The results presented in this study indicate the main problems related to the performance of plumbing fixtures installed in public sports facilities in Joinville and can be useful in planning building preventive maintenance and water conservation actions.